2019
DOI: 10.1097/md.0000000000015921
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1 polymorphisms modulate the susceptibility to osteonecrosis of the femoral head among Chinese Han population

Abstract: The study was performed to investigate the genetic associations of IGF-1 polymorphisms rs35767, rs5742714, and rs972936 with susceptibility to osteonecrosis of the femoral head (ONFH) among Chinese Han population. Totally, 101 ONFH patients and 128 healthy controls were enrolled. Hardy–Weinberg equilibrium (HWE) was detected with chi-square test in control group. Odds ratios (ORs) with 95% confidence intervals (95% CIs) were calculated to estimate the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Osteonecrosis of the femoral head (ONFH) is an obstinate bone illness resulting in collapse of the femoral head and movement disorder of hip joint [1]. The performance of ONFH may be painless, but serious pain and loss of movement show up by and large [2].…”
Section: Introductionmentioning
confidence: 99%
“…Osteonecrosis of the femoral head (ONFH) is an obstinate bone illness resulting in collapse of the femoral head and movement disorder of hip joint [1]. The performance of ONFH may be painless, but serious pain and loss of movement show up by and large [2].…”
Section: Introductionmentioning
confidence: 99%
“…Through Hardy–Weinberg equilibrium test and haplotype analysis, Wang et al found that IGF1 polymorphism was closely related to the susceptibility to osteonecrosis of the femoral head. [ 12 ] Familial osteonecrosis of the femoral head is typically inherited as an autosomal dominant trait, [ 13 ] and thus offspring are likely to have the same genetic mutation leading to the disease. Existing gene detection techniques can be used to provide molecular prenatal diagnosis along with further genetic counseling to enable early and effective interventions and treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on rabbits with steroid-induced ONFH, IGF-1 was measured via enzyme-linked immunosorbent assay at 4, 8, and 16 weeks, and the results revealed that IGF-1 expression began to increase 4 weeks earlier than the appearance of abnormal bone marrow tissue in rabbits (Saygun et al, 2012;Xu et al, 2021). Wang et al (2019) investigated the genetic association between the IGF-1 polymorphisms rs35767, rs5742714, and rs972936 and susceptibility to ONFH among the Han Chinese population (101 patients with ONFH and 128 healthy individuals). Significant differences were observed in the three polymorphisms between ONFH and control groups.…”
Section: Insulin-like Growth Factor-1mentioning
confidence: 99%
“… Wang et al (2019) investigated the genetic association between the IGF-1 polymorphisms rs35767, rs5742714, and rs972936 and susceptibility to ONFH among the Han Chinese population (101 patients with ONFH and 128 healthy individuals). Significant differences were observed in the three polymorphisms between ONFH and control groups.…”
Section: Association Between the Polymorphisms Of Growth Factor-relat...mentioning
confidence: 99%